Упростим сначала 1) 4x+20+2y-12=1-3y 4x+5y=1+12-20 4x+5y=-7 2) 3y+12+6x-7=2+4x 2x+3y=2+7-12 2x+3y=-3 3) 4x+5y=-7 2x+3y=-3 | домножим на 2
4x+5y=-7 4x+6y=-6 Вычтем из 2 уравнения 1, получим: y=1 Подставим y в любое из уравнений, например, в 1, тогда: 4x+5*1=-7 4x+5=-7 4x=-12 x=-3 (-3;1) - решение системы ответ: (-3;1)
1) 4x+20+2y-12=1-3y
4x+5y=1+12-20
4x+5y=-7
2) 3y+12+6x-7=2+4x
2x+3y=2+7-12
2x+3y=-3
3) 4x+5y=-7
2x+3y=-3 | домножим на 2
4x+5y=-7
4x+6y=-6
Вычтем из 2 уравнения 1, получим:
y=1
Подставим y в любое из уравнений, например, в 1, тогда:
4x+5*1=-7
4x+5=-7
4x=-12
x=-3
(-3;1) - решение системы
ответ: (-3;1)